Refleksi “Kemerdekaan” Warganet dalam Kolom Komentar Akun Media Sosial Jokowi dan Ma’ruf Amin: Kajian Pargmatik - Lisnawaty Simatupang (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2022)
The conditions, expressions, a priori, and people's views about independence are expected to be reflected through communication and interaction between the community and the government on various social media platforms. However, there are few studies that examine various notions and a priori independence that have arisen in society. As a result, this study examines society's opinions (netizen) on independence as stated in their comments. The researcher classifies speech forms, implicatures, and reflections of independence to fully comprehend the meaning of each comment. Assertive, expressive, and directive speech were found to be the most frequently applied forms of speech. Implications can be seen in the form of satire in netizen comments. 57.7% of comments reflect those netizens also feel